Preparation method and application of lithium titanium aluminum phosphate solid electrolyte

The preparation of titanium aluminum phosphate by combining liquid phase and solid phase is solved, and the problems of high energy consumption, uneven particle size and low yield in the existing synthesis process are achieved, and the preparation of high purity and uniform particles is achieved, and the process is stable, efficient and cost is low.

CN119503754APending Publication Date: 2025-02-25HENAN BAILI NEW ENERGY MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411682330.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the existing synthesis process of titanium aluminum lithium lithium phosphate solid electrolyte, the solid phase synthesis method has problems of high energy consumption and uneven grain size, while the liquid phase synthesis method has problems of small product particle size and low yield.

Method used

By combining liquid phase and solid phase, a solution containing a titanium source, a phosphorus source and an aluminum source is configured, the pH is adjusted to acidity and a solvent-thermal reaction is carried out to obtain a solid phase, and mixed with a lithium source to grind it, and lithium titanium aluminum phosphate is obtained through two-stage sintering.

Benefits of technology

Effectively prepare the lithium titanium aluminum phosphate product with high purity, fine particles and uniformity, and the preparation method is stable, the output efficiency is high, the cost is low, the raw materials are easy to obtain, and the environment is friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503754A_ABST
    Figure CN119503754A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a lithium titanium aluminum phosphate solid electrolyte, and relates to the technical field of solid electrolytes. Specifically, the method comprises the following steps: firstly, preparing a solution containing a titanium source, a phosphorus source and an aluminum source, adjusting the pH value to be acidic, carrying out solvothermal reaction, and carrying out solid-liquid separation to obtain a solid phase; and mixing and grinding the dried solid phase and a lithium source, and carrying out two-stage sintering to obtain the titanium aluminum lithium phosphate. According to the invention, the technical defects of high energy consumption and non-uniform grain size of a solid-phase synthesis method in the existing synthesis process and low grain size and low yield of a product in a liquid-phase synthesis method can be effectively overcome; according to the preparation method, high-purity, uniform-particle-size and fine lithium titanium aluminum phosphate can be obtained, when the lithium titanium aluminum phosphate is used for a solid electrolyte of a lithium battery, the electrolyte structure can be optimized, the ionic conductivity can be improved, the preparation process is simple and easy to implement, and popularization and application during batch production are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a preparation method and application of a lithium aluminum titanium phosphate solid electrolyte. Background Art

[0002] Liquid electrolytes are usually used in existing lithium-ion batteries, but once the organic electrolyte leaks, the probability of the battery exploding at high temperatures increases, posing a major safety hazard. Solid electrolytes can serve as both a medium for ion conduction and a diaphragm to prevent the conduction of electrons and prevent battery short circuits. They have the functions of both liquid electrolytes and diaphragms and have received widespread attention. Compared with electrolytes, solid electrolytes have extremely high safety and volume density, which helps to improve the energy density of the battery and have better performance in battery temperature environment, electrochemical window, and electrochemical stability.

[0003] At present, solid electrolytes mainly include inorganic electrolytes, organic polymer electrolytes or composite electrolytes, among which inorganic electrolytes further include oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, etc. NASICON-type oxides are oxide solid electrolytes, also known as sodium oxide superionic conductors, which have been widely studied due to their advantages such as three-dimensional ion transport framework and easy synthesis; lithium aluminum titanium phosphate (LATP), as a NASICON-type oxide, has great application potential in solid electrolytes due to its good chemical stability and excellent mechanical properties.

[0004] The current methods for preparing lithium aluminum titanium phosphate include: solid-phase synthesis methods (such as melt quenching method, high-temperature solid-phase reaction method) have the advantages of high selectivity and high yield, but also have disadvantages such as high energy consumption, uneven grain size, and easy agglomeration; liquid-phase synthesis methods (such as coprecipitation method, sol-gel method) do not require high thermal temperature, but the obtained powder product has a small particle size and low yield, which is difficult to meet the needs of mass production.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The first purpose of the present invention is to provide a method for preparing a lithium aluminum titanium phosphate solid electrolyte, which is used to solve the technical defects of high energy consumption and uneven grain size in the solid phase synthesis method in the existing synthesis process, and low product particle size and low yield in the liquid phase synthesis method.

[0007] The second purpose of the present invention is to provide an electrolyte for lithium-ion batteries. By introducing a lithium aluminum titanium phosphate solid electrolyte prepared by a specific process route, it can help optimize the electrolyte structure and improve the ionic conductivity.

[0008] The third purpose of the present invention is to provide a lithium-ion battery, which helps to reduce the defects of internal stress concentration in lithium batteries and reduce the risks of short circuit and dendrite growth by introducing a lithium aluminum titanium phosphate solid electrolyte prepared by a specific process route.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] A method for preparing a lithium aluminum titanium phosphate solid electrolyte comprises the following steps:

[0011] (1) preparing a solution containing a titanium source, a phosphorus source, and an aluminum source, adjusting the pH to an acidic state, performing a solvothermal reaction, and performing solid-liquid separation to obtain a solid phase;

[0012] (2) The dried solid phase is mixed with a lithium source and ground, and then subjected to two-stage sintering to obtain lithium aluminum titanium phosphate.

[0013] An electrolyte for lithium-ion batteries comprises an electrolyte prepared by the preparation method of lithium aluminum titanium phosphate solid electrolyte.

[0014] A lithium ion battery comprises an electrolyte prepared by the preparation method of lithium aluminum titanium phosphate solid electrolyte.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The present invention provides a method for preparing a lithium titanium aluminum phosphate solid electrolyte. By adopting a method combining a liquid phase and a solid phase, a lithium titanium aluminum phosphate product with high purity, fine particles and uniformity can be effectively prepared, and the preparation method is stable and has high output efficiency. The preparation method of the present invention is simple and easy to implement, and has low cost and easy-to-obtain raw materials. No organic solvents such as solvents or complexing agents are added during the preparation process, and the preparation is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 The XRD spectrum of lithium aluminum titanium phosphate prepared in Example 1 of the present invention is provided. DETAILED DESCRIPTION

[0019] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but those skilled in the art will appreciate that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. In addition, the terms "first", "second" and "third" are only used for descriptive purposes and cannot be interpreted as indicating or implying relative importance.

[0020] The first aspect of the present invention is to provide a method for preparing a lithium aluminum titanium phosphate solid electrolyte.

[0021] Regarding the existing synthesis routes of lithium aluminum titanium phosphate solid electrolytes: (a) The solid phase method usually includes high-temperature sintering, that is, the raw materials such as lithium source, aluminum source, titanium source and phosphoric acid in the configured dosage ratio are fully mixed and ground, and then granulated or other molding treatments such as binders are performed, and then sintered at high temperature to obtain lithium aluminum titanium phosphate with a specific density and conductivity. In the solid phase method, even if the parameters such as the heating rate, sintering temperature and holding time during the sintering process are strictly controlled, it is inevitable that there will be defects such as grain agglomeration and uneven grain size, and these defects are difficult to compensate for by secondary grinding. (b) Liquid phase methods such as co-precipitation methods are to generate precipitates by using a precipitant to generate precipitates in a solvent with the configured dosage ratio of lithium source, aluminum source, titanium source and phosphoric acid, and then sinter to obtain low-particle-size, low-purity powdered lithium aluminum titanium phosphate, and the yield is low.

[0022] The present invention adopts a method combining a liquid phase (coprecipitation method) and a solid phase (grinding and calcining) to effectively and comprehensively solve the inherent defects of the above method, and obtain a lithium aluminum titanium phosphate solid electrolyte with uniform particle size, low particle size, high purity, simple preparation process and low cost. The preparation method of the present invention mainly includes the following steps, wherein step (1) mainly involves the liquid phase operation part, step (2) mainly involves the solid phase operation part, and the timing of inputting each raw material and the operation sequence are described.

[0023] (1) A solution containing a titanium source, a phosphorus source and an aluminum source is prepared, the pH is adjusted and a solvothermal reaction is performed, and a solid phase is obtained by solid-liquid separation.

[0024] As a preferred embodiment, the titanium source includes at least one of titanium oxychloride, titanium oxysulfate, metatitanic acid or titanium tetrachloride.

[0025] As a preferred embodiment, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate or ammonium phosphate.

[0026] As a preferred embodiment, the aluminum source includes at least one of aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum chloride, aluminum oxide or aluminum hydroxide.

[0027] As a preferred embodiment, the molar ratio of the titanium source, the aluminum source and the phosphorus source is (1.5-1.7): (0.3-0.5): 3, based on the titanium atoms in the titanium source, the phosphorus atoms in the phosphorus source and the aluminum atoms in the aluminum source. It can be understood that by limiting the usage ratio of the titanium source, the phosphorus source and the aluminum source within the above range, lithium aluminum titanium phosphate with a specific molecular formula can be effectively prepared by liquid phase precipitation, so that it has a good crystal structure.

[0028] As a preferred embodiment, a solution containing the titanium source is first prepared, and then the phosphorus source is added to perform a first mixing, and then the aluminum source is added to perform a second mixing, which helps to obtain a uniformly dispersed reaction liquid system. It can be understood that both the first mixing and the second mixing can be assisted by oscillation, stirring, centrifugation, ultrasound, etc., which helps to accelerate dispersion and obtain a relatively uniform dispersed system.

[0029] As a preferred embodiment, in the solution containing the titanium source, the phosphorus source and the aluminum source, the solution concentration is 1 mol / L to 4 mol / L in terms of the amount of titanium atoms. It can be understood that the amount of solvent (water) added can be controlled within a reasonable range through the above concentration limit, which helps to control the rate of the precipitation reaction and make the particle size of the precursor obtained by precipitation relatively uniform.

[0030] As a preferred embodiment, the pH is adjusted to 3-6; in some optional embodiments, the pH range includes but is not limited to any point value among 3, 3.5, 4, 4.5, 5, 5.5, 6 or a numerical interval consisting of any two values.

[0031] As a more preferred embodiment, due to the specific raw material selection of the titanium source, the phosphorus source and the aluminum source, the reaction solution is usually strongly acidic, and the pH is adjusted to 3-6 by an alkaline reagent and a subsequent solvent thermal reaction is carried out; wherein the alkaline reagent includes at least one of ammonia water, sodium hydroxide, sodium carbonate, ammonium carbonate or potassium hydroxide.

[0032] As a preferred embodiment, the temperature of the solvothermal reaction is 40°C to 100°C, and the time of the solvothermal reaction is 2h to 4h; in some optional embodiments, the temperature of the solvothermal reaction includes but is not limited to any point value among 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 (°C) or a numerical range formed by any two values, and the time of the solvothermal reaction includes but is not limited to any point value among 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4 (h) or a numerical range formed by any two values.

[0033] It can be understood that the present invention limits the processing temperature and processing time in the solvent thermal reaction to the above ranges respectively. On the one hand, when the temperature is too low, the molecular thermal motion is not obvious enough, so it can only be compensated by the reaction time; on the other hand, the molecular activity and molecular thermal motion will be too high, and the evaporation of the solvent may affect the reaction process and cause a waste of heat resources. Therefore, the temperature and time of the solvent thermal reaction are limited to the above range.

[0034] As a preferred embodiment, the solid-liquid separation includes but is not limited to decantation, filtration, centrifugation, filter or membrane separation, etc.; in a more preferred embodiment, the solid-liquid separation in this step adopts suction filtration to perform solid-liquid separation in a low-yield production mode or a laboratory scenario, and can be performed by a filter in a large-scale batch production mode.

[0035] As a preferred embodiment, step (1) further comprises: drying the solid phase after the solid-liquid separation; in some more preferred embodiments, the drying temperature is 100°C to 140°C, and the drying time is 12h to 48h. In some optional embodiments, the drying temperature includes but is not limited to any point value among 100, 105, 110, 115, 120, 125, 130, 135, 140 (°C) or a numerical interval consisting of any two values, and the drying time includes but is not limited to any point value among 12, 15, 20, 25, 30, 35, 40, 45, 48 (h) or a numerical interval consisting of any two values.

[0036] (2) The dried solid phase is mixed with a lithium source and ground, and then subjected to two-stage sintering to obtain lithium aluminum titanium phosphate.

[0037] As a preferred embodiment, based on the lithium atoms in the lithium source and the titanium atoms in the solid phase, the molar ratio of the lithium source to the solid phase is (1.3-1.5): (1.5-1.7).

[0038] In the present invention, the lithium source, aluminum source, titanium source and phosphorus source should satisfy the following chemical formula: Li1+x Al x Ti 2x (PO4)3, wherein x is selected from 0.3 to 0.5; in some optional embodiments, x includes but is not limited to any point value among 0.3, 0.32, 0.34, 0.35, 0.36, 0.38, 0.4, 0.42, 0.44, 0.45, 0.46, 0.48, 0.5, or a numerical interval consisting of any two numerical values.

[0039] As a preferred embodiment, the lithium source includes at least one of lithium carbonate, lithium phosphate, lithium hydroxide, lithium nitrate or lithium oxide.

[0040] As a preferred embodiment, the grinding includes but is not limited to mechanical grinding, ball milling, ultrasonic grinding, etc.; in some more preferred embodiments, the grinding is performed by ball milling, and the grinding time is 0.5h to 1.5h.

[0041] As a preferred embodiment, the average particle size of the ground material is 0.4 μm to 0.6 μm. In the present invention, the solid phase material is mixed by grinding, which can not only play the role of mixing the reaction raw materials evenly, but also play the role of refining the particle size of the raw materials, thereby facilitating the subsequent sintering to obtain a lithium aluminum titanium phosphate product with uniform particle size.

[0042] As a preferred embodiment, the two-stage sintering includes a first sintering and a second sintering; wherein, the temperature of the first sintering is 350°C to 650°C, the duration of the first sintering is 4h to 8h, the temperature of the second sintering is 700°C to 900°C, and the duration of the second sintering is 4h to 8h.

[0043] In the present invention, the two-stage sintering includes a low-temperature pre-sintering stage and a high-temperature sintering stage; wherein the low-temperature pre-sintering can effectively reduce the initial reaction temperature of the precursor, thereby inhibiting the abnormal growth of lithium aluminum titanium phosphate grains at high temperatures; the growth process of the grains is precisely controlled by the two-stage sintering, thereby obtaining lithium aluminum titanium phosphate with a more uniform particle size. In the present invention, by limiting the temperature and time specifically used in the two-stage sintering, the problems of grain agglomeration defects and uneven grain size are effectively avoided.

[0044] As an optional embodiment, the temperature of the first sintering includes but is not limited to any point value among 350, 400, 450, 500, 550, 600, 650 (℃) or a numerical range formed by any two values, and the duration of the first sintering includes but is not limited to any point value among 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8 (h) or a numerical range formed by any two values.

[0045] As an optional embodiment, the temperature of the second sintering includes but is not limited to any point value among 700, 720, 750, 780, 800, 820, 850, 880, 900 (℃) or a numerical range formed by any two values, and the duration of the second sintering includes but is not limited to any point value among 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8 (h) or a numerical range formed by any two values.

[0046] The second aspect of the present invention is to provide an electrolyte for lithium ion batteries, wherein the electrolyte for lithium ion batteries comprises an electrolyte prepared by the preparation method of lithium titanium aluminum phosphate solid electrolyte as described in the first aspect.

[0047] It should be noted that in the second aspect of the present invention, the electrolyte for lithium-ion batteries is not limited to a solid electrolyte or a semi-solid electrolyte, and similarly, there is no limitation on the components of the electrolyte for lithium-ion batteries other than lithium aluminum titanium phosphate.

[0048] It is understandable that the electrolyte for lithium-ion batteries described in the present invention, in addition to the electrolyte prepared by the preparation method of the lithium aluminum titanium phosphate solid electrolyte, can also include any other conventional or unconventional electrolyte components and be formulated to obtain a composite electrolyte product.

[0049] In some optional embodiments, in the second aspect of the present invention, the electrolyte prepared based on the preparation method of the lithium titanium aluminum phosphate solid electrolyte can be further modified, including but not limited to carbon coating, element or additive doping, etc., and the present invention does not impose any restrictions on the above-mentioned composite components or modification techniques.

[0050] The third aspect of the present invention is to provide a lithium ion battery, wherein the lithium ion battery comprises an electrolyte prepared by the preparation method of lithium titanium aluminum phosphate solid electrolyte as described in the first aspect.

[0051] It is understandable that the lithium-ion battery should include at least a positive electrode and a negative electrode, but the third aspect of the present invention does not impose any restrictions on the specific selection of the above electrodes; the lithium-ion battery may also include other necessary or unnecessary functional elements or packaging components, such as a diaphragm, a housing, a safety valve, etc., and those skilled in the art may make any selections thereof. When the lithium-ion battery includes the lithium aluminum titanium phosphate solid electrolyte as described in the first aspect, whether or not other electrolytes or any other functional components or structures are used in the lithium-ion battery, it can be regarded as an embodiment of the present invention.

[0052] Example 1

[0053] S1: Mixing a titanium source solution (aqueous solution of titanium tetrachloride, with a concentration of 2 mol / L) and a phosphorus source (diammonium hydrogen phosphate) and stirring to obtain a mixture A;

[0054] S2: adding an aluminum source (aluminum chloride) to mixture A and stirring to obtain mixture B; wherein the molar ratio of Al, Ti, and P is 0.4:1.6:3;

[0055] S3: Use alkaline solution (ammonia water) to adjust the pH of mixture B to 4, stir and react at 70°C for 3h, and obtain precipitate C after suction filtration;

[0056] S4: drying the precipitate C at 120° C. for 20 h to obtain a precipitate D;

[0057] S5: grinding the precipitate D and the lithium source (lithium nitrate) for 1 h to obtain a mixture E with a particle size of 0.55 μm; wherein the molar ratio of Li to Al is 1.4:0.4;

[0058] S6: sintering the mixture E for the first time at 500° C. for 6 h to obtain a mixture F;

[0059] S7: sintering the mixture F for a second time at 800° C. for 6 hours to obtain the lithium aluminum titanium phosphate of this embodiment.

[0060] The lithium aluminum titanium phosphate prepared in this example was subjected to XRD test. Figure 1 The test results are shown. Figure 1 A standard XRD card of lithium titanium phosphate (PDF#35-0754) is also provided as a control.

[0061] Example 2

[0062] It is basically the same as Example 1, except that the titanium source is replaced by titanium dichloride, the phosphorus source is replaced by phosphoric acid and ammonium phosphate (molar ratio 1:1), the aluminum source is replaced by aluminum oxide, and the lithium source is replaced by lithium carbonate.

[0063] Example 3

[0064] It is basically the same as Example 1, except that the titanium source is replaced by titanyl sulfate, the phosphorus source is replaced by phosphoric acid and ammonium dihydrogen phosphate (molar ratio 1:1), the aluminum source is replaced by aluminum hydroxide, and the lithium source is replaced by lithium hydroxide.

[0065] Example 4

[0066] It is basically the same as Example 1, except that:

[0067] In step S6, the first sintering is performed at 350° C. for 8 hours; and in step S7, the second sintering is performed at 700° C. for 8 hours.

[0068] Example 5

[0069] It is basically the same as Example 1, except that:

[0070] In step S6, the first sintering is performed at 650°C for 4 hours; in step S7, the second sintering is performed at 800°C for 4 hours.

[0071] Example 6

[0072] It is basically the same as Example 1, except that:

[0073] The molar ratio of Al, Ti and P in step S2 is 0.3:1.7:3; the molar ratio of Li and Al in step S5 is 1.3:0.3.

[0074] Example 7

[0075] It is basically the same as Example 1, except that:

[0076] The molar ratio of Al, Ti and P in step S2 is 0.5:1.5:3; the molar ratio of Li and Al in step S5 is 1.5:0.5.

[0077] Comparative Example 1

[0078] The method is basically the same as Example 1, except that steps S6 and S7 are replaced by:

[0079] S6: The mixture E is sintered for the first time at 800° C. for 12 h to obtain lithium aluminum titanium phosphate of this comparative example.

[0080] Comparative Example 2

[0081] The method is basically the same as Example 1, except that step S5 is cancelled and step S2 is replaced by:

[0082] S2: adding an aluminum source (aluminum chloride) and a lithium source (lithium nitrate) to mixture A, stirring to obtain mixture B; wherein the molar ratio of Li, Al, Ti, and P is 1.4:0.4:1.6:3.

[0083] Table 1

[0084]

[0085] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A method for preparing a lithium aluminum titanium phosphate solid electrolyte, characterized in that: The steps include: (1) preparing a solution containing a titanium source, a phosphorus source, and an aluminum source, adjusting the pH to an acidic state, performing a solvothermal reaction, and performing solid-liquid separation to obtain a solid phase; (2) The dried solid phase is mixed with a lithium source and ground, and then subjected to two-stage sintering to obtain lithium aluminum titanium phosphate.

2. The method for preparing the lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: The titanium source includes at least one of titanium dichloride, titanium sulfate, metatitanic acid or titanium tetrachloride; and / or, the phosphorus source comprises at least one of phosphoric acid, diammonium phosphate, diammonium hydrogen phosphate or ammonium phosphate; and / or, the aluminum source comprises at least one of aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum chloride, aluminum oxide or aluminum hydroxide; And / or, the lithium source includes at least one of lithium carbonate, lithium phosphate, lithium hydroxide, lithium nitrate or lithium oxide.

3. The method for preparing the lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: Calculated based on the titanium atoms in the titanium source, the phosphorus atoms in the phosphorus source and the aluminum atoms in the aluminum source, the molar ratio of the titanium source, the aluminum source and the phosphorus source is (1.5-1.7):(0.3-0.5):

3.

4. The method for preparing the lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: In step (1), the pH is adjusted to 3-6; Preferably, the pH is adjusted by an alkaline agent, and the alkaline agent includes at least one of ammonia water, sodium hydroxide, sodium carbonate, ammonium carbonate or potassium hydroxide.

5. The method for preparing the lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: The temperature of the solvent thermal reaction is 40° C. to 100° C., and the time of the solvent thermal reaction is 2 h to 4 h.

6. The method for preparing the lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: drying the solid phase after the solid-liquid separation; The drying temperature is 100° C. to 140° C., and the drying time is 12 h to 48 h.

7. The method for preparing the lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: Calculated based on the lithium atoms in the lithium source and the titanium atoms in the solid phase, the molar ratio of the lithium source to the solid phase is (1.3-1.5):(1.5-1.7).

8. The method for preparing lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: The two-stage sintering includes a first sintering and a second sintering; wherein the temperature of the first sintering is 350°C to 650°C, the duration of the first sintering is 4h to 8h, the temperature of the second sintering is 700°C to 900°C, and the duration of the second sintering is 4h to 8h.

9. An electrolyte for a lithium ion battery, characterized in that An electrolyte comprising the electrolyte prepared by the method for preparing the lithium titanium aluminum phosphate solid electrolyte as described in any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: An electrolyte comprising the electrolyte prepared by the method for preparing the lithium titanium aluminum phosphate solid electrolyte as described in any one of claims 1 to 8.